Thermal history due to laser heating of solid surfaces - Semchuk, O.Yu.; Lerman, L.B.; Willander, M.; Nur, O. (Поверхность, 2011)
Using the finite integral transformation along the spatial Cartesian coordinates, an analytical expression for calculating the temperature distribution T (x, y, z) due to laser pulses in a solid located in the half-space z<0 is obtained. The numerical calculations show that a uniform warming of the body surface takes place only during a part of the pulse duration. Deep inside the solid, the maximum temperature value compared to the surface takes place with a time delay. This time delay depends on the heat wave propagation velocity. Along with heat penetration into the solid, a maximum temperature zone degradation process takes place. Cooling velocity in the upper layers appears to be higher than that in the deeper layers. However, the cooling period in deeper layers is less than that in upper layers. The results obtained are qualitatively consistent with published experimental data. За допомогою кінцевого інтегрального перетворення по декартових координатах в площині поверхні отримано аналітичний вираз для розподілу температури Т(x,y,z) в зразку, що займає напівпростір z<0. Проведені чисельні розрахунки показали, що в більш глибоких шарах значення температури досягається пізніше, ніж на поверхні, оскільки нижніх шарів теплова хвиля досягає пізніше. Швидкість охолодження нижніх шарів менша, ніж верхніх. Крім того, чисельні розрахунки показали, що максимальна температура на заданій глибині слабко залежить від форми розподілу інтенсивності в лазерному пучку. Отримані результати якісно співпадають з експериментальними даними. С помощью конечного интегрального преобразования по декартовым координатам в плоскости поверхности получено аналитическое выражение для распределения температуры Т(x,y,z) в образце, занимающем полупространство z<0. Проведенные численные расчеты показали, что в более глубоких слоях максимальное значение температуры достигается позже, чем на поверхности, поскольку в нижние слои тепловая волна доходит позже. Скорость охлаждения верхних слоев оказывается больше, чем нижних, однако время охлаждения нижних слоев меньше, чем верхних. Кроме того, численные расчеты показали, что максимальная температура на заданной глубине слабо зависит от формы распределения интенсивности в лазерном пучке. Полученные результаты качественно совпадают с экспериментальными данными.